Approach to patient with cough by American and Chinese respiratory specialist. (August 2021) - Liu, Xiuxiu; Kesebir, Deniz; Kazachkov, Mikhail
Highlights: Integrating Traditional Chinese Medicine (TCM) with Western Medicine terminology should facilitate our understanding. The approach to pediatric cough from TCM and Western Medicine point of view is to eliminate the imbalance in the body and restoring the Qi flow. TCM gaining in popularity in Western Medicine and may provide additional treatment options and need further investigations. Abstract: Cough is a common pediatric condition. Acute cough is often considered to be self-limiting and not requiring clinical management. However, pediatric patients and their parents often seek remedies for an acute cough. Traditional Chinese Medicine (TCM) specialists have been treating pediatric cough for millennia. Here we present a case of pediatric cough and the approaches taken to it by a Western and Chinese respiratory specialist. We conclude that TCM may provide important and useful insights into the treatment of such pediatric respiratory disease.